SPECTRUM OF CENTRAL NERVOUS SYSTEM TUMOURS-A SINGLE CENTER HISTOPATHOLOGICAL REVIEW OF 761 CASES OVER 5 YEARS - Ahsan, Javaria; Hashmi, Shohaib Naiyar; Muhammad, Iqbal; Din, Hafeez Ud; Butt, Ahsan Masood; Nazir, Sajid; Azhar, Muhammad (Journal of Ayub Medical College Abbottabad, 2015)
Background: The incidence of central nervous system (CNS) tumours has rapidly increased over the past few years. There is no accurate nationwide CNS tumour epidemiology in Pakistan that makes policy making for tumour screening and early treatment difficult. The purpose of this study was to provide the spectrum of CNS tumours in a premier diagnostic and referral centre of Pakistan. Methods: This cross-sectional study was carried out at Histopathology Department, Armed Forces Institute of Pathology over a period of 5 years. A total of 761 cases patients who were diagnosed with CNS tumours on histopathology, both benign and malignant, belonging to both genders, between the ages of 1-85 years, from 11.2009 to 31.12.2013 were included in the study. Results: Seven CNS tumour categories were as follows; tumours of neuroepithelial tissue (56.0%), tumours of the meninges (28.3%), tumour of the sellar region (2.6%), germ cell tumour (0.1), tumour of cranial and paraspinal nerves (5.4%), lymphomas and haematopoietic neoplasm (2.4%), metastatic tumours (4.9%), where histological types by age and gender showed great variability. Astrocytic tumours were the commonest neuroepithelial tumours (69.4%). Glioblastoma multiform forming the largest subtype of neuroepithelial tumours (40.4%) with a mean age at diagnosis being 47.1 years. Overall, males exceeded females in number of most of the CNS tumour types, however meningeal tumours were more frequently noted in females. Conclusions: Neuroepithelial tumours are commonest tumour and comprise more than half of all operated CNS tumours in our setup, followed by meningeal tumours. Glioblastoma multiforme is largest subtype of neuroepithelial tumour, and comprising 40.4% of all. Keywords: Central nervous system, Neuroepithelial tumours, Meningeal tumours, Glioblastoma multiforme